2009
DOI: 10.1089/neu.2008.0776
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-Ryk Signaling Mediates Axon Growth Inhibition and Limits Functional Recovery after Spinal Cord Injury

Abstract: Wnt proteins are a large family of diffusible factors that play important roles in embryonic development, including axis patterning, cell fate specification, proliferation, and axon development. It was recently demonstrated that Ryk (receptor related to tyrosine kinase) is a conserved high-affinity Wnt receptor, and that Ryk-Wnt interactions guide corticospinal axons down the spinal cord during development. Here, we report that the Ryk-Wnt signal mediates the inhibition of corticospinal axon growth in the adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
77
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 29 publications
2
77
0
Order By: Relevance
“…[3][4][5] A growing body of evidence suggests that Wnt signalling may be involved in homeostasis and disease progression in adult tissues, [6][7][8][9][10][11] including the spinal cord. 10,[12][13][14][15][16] Consistent with these findings, we have previously shown that most of Wnt ligands and inhibitors are expressed in the adult spinal cord of rats and, following SCI, are differentially induced with at least Wnt/b-catenin signalling activation in cells that appear to be involved in glial scarring. 13 Strategies seeking to modulate Wnt-dependent signaling pathways have been shown to be beneficial in different experimental models of CNS disorders 8,[17][18][19][20][21][22][23] including SCI.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…[3][4][5] A growing body of evidence suggests that Wnt signalling may be involved in homeostasis and disease progression in adult tissues, [6][7][8][9][10][11] including the spinal cord. 10,[12][13][14][15][16] Consistent with these findings, we have previously shown that most of Wnt ligands and inhibitors are expressed in the adult spinal cord of rats and, following SCI, are differentially induced with at least Wnt/b-catenin signalling activation in cells that appear to be involved in glial scarring. 13 Strategies seeking to modulate Wnt-dependent signaling pathways have been shown to be beneficial in different experimental models of CNS disorders 8,[17][18][19][20][21][22][23] including SCI.…”
mentioning
confidence: 99%
“…13 Strategies seeking to modulate Wnt-dependent signaling pathways have been shown to be beneficial in different experimental models of CNS disorders 8,[17][18][19][20][21][22][23] including SCI. 10,14,24 Ryk is a well-known unconventional Wnt receptor 25 that is composed of a Wnt inhibitory factor 1 (WIF1)-like extracellular domain that enables its interaction with different Wnt ligands. This is in addition to an intracellular domain that is catalytically inactive because of specific amino acid substitutions, 26 although Ryk receptor is known to transduce extracellular signals across the plasma membrane through several mechanisms.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The corticospinal tract has proven reticent to nearly all experimental attempts to promote long-distance regeneration, though it has been shown to be capable of spontaneous short-range sprouting [85,86]. However, this sprouting is limited by the re-induction of Ryk expression within the lesioned corticospinal axons [75,87]. During development, Ryk expressing corticospinal axons encounter a decreasing gradient of Wnts that propels them caudally; meanwhile, injured corticospinal axons face an abrupt barrier of expressed Wnts surrounding the injury site (Fig.…”
Section: Dorsal Columnmentioning
confidence: 99%